2011
DOI: 10.1016/j.annepidem.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Disparities in Cardiovascular Disease: Birth Weight, Body Mass Index, and Young Adult Systolic Blood Pressure in the National Longitudinal Study of Adolescent Health

Abstract: PURPOSE We evaluated the contributions of birth weight and current body mass index (BMI) to racial/ethnic disparities in systolic blood pressure (SBP) in the U.S. METHODS Participants were 10,046 young adults (ages 24 – 32) in the National Longitudinal Study of Adolescent Health (Add Health). SBP, BMI, and other contemporaneous factors were assessed at Wave IV (2007–2008); birth weight and other early life factors were reported at Wave I (1994–1995). Data were analyzed using sex- and race-stratified multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…[145][146][147] This finding might suggest that current BMI has a greater impact on blood pressure than does birth weight or prematurity, which could reflect the impact of rapid catch-up growth experienced as a result of being born small. 14 Postnatal catch-up growth is encouraged in LBW and premature infants in developing countries with the goal of improving resistance to infections and reducing stunting and ongoing malnutrition, which remain common in these regions.…”
Section: Obstruction Of the Developing Kidneymentioning
confidence: 98%
“…[145][146][147] This finding might suggest that current BMI has a greater impact on blood pressure than does birth weight or prematurity, which could reflect the impact of rapid catch-up growth experienced as a result of being born small. 14 Postnatal catch-up growth is encouraged in LBW and premature infants in developing countries with the goal of improving resistance to infections and reducing stunting and ongoing malnutrition, which remain common in these regions.…”
Section: Obstruction Of the Developing Kidneymentioning
confidence: 98%
“…While the risk of hypertension increases dramatically with age, the incidence of hypertension is growing among younger populations [2]. Using measured systolic blood pressure, two recent studies using the National Longitudinal Study of Adolescent Health data found that 12 % of U.S. young adults had systolic blood pressure >140 mm HG [3, 4]. Compared to the large body of work that has examined disparities related to the mental and sexual health of gay and bisexual men and women, little work has investigated physical health disparities among this population and addressing this gap in the literature was recently recognized as a Healthy People 2020 Objective [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…, Richardson et al . ). Furthermore, the exact mechanism(s) that contribute to the sex difference in adult blood pressure following an insult during early life have not yet been fully elucidated.…”
mentioning
confidence: 97%